Peran Bank Jangkar dalam Arsitektur Perbankan Indonesia - Noerlina, Noerlina; Gautama, Idris (Bina Nusantara University, 2005)
Anchor bank (Bank Jangkar) is a hot issue in bank business recently. This article tries to elaborate requirements that related to anchor bank. The beginning of this article will explain the understanding Indonesia Bank Architecture, anchor bank, the prerequisite needed to become anchor bank then the prerequisite elements will be explained. Tables and figures related to explanation are also provided. At the end of this paper, conclusions and suggestions will be made.Â